Digitized Labor The Impact of the Internet on Employment (Springer International Publishing, 2018)
As with previous technological revolutions, innovations in the online world have triggered transformations in the labor market and the economy. While the Internet is trumpeted as a great job creator, there are also downsides that need to be identified and dealt with. The book discusses the following topics: Is the Internet a net creator of jobs? How are job profiles changed by the digital economy? What are the impacts on income distribution? Is it a winner-takes-all tournament? What models can facilitate adjustment without slowing innovation? This book features essays from major experts in the field coming from academia, international organizations, the private sector, and civil society. It blends theoretical and applied research presenting results from many countries, with particular emphasis on Europe, the USA, Canada and Asia.